Preoperative planning using the picture archiving and communication system technique in high tibial osteotomy. (30th January 2017) - Kim, Hee-June; Lee, Hyun-Joo; Shin, Ji-Yeon; Park, Kyeong-Hyeon; Min, Seung-Gi; Kyung, Hee-Soo
Purpose: This study aimed to evaluate the accuracy of the picture archiving and communication system (PACS) method in order to select the correction angle and gap in open-wedge high tibial osteotomy (HTO) and clinical results of the patients. Material and methods: This retrospective study analyzed 27 consecutive patients (30 knees) underwent open-wedge HTO using the PACS method between April 2013 and March 2015. Full-length lower limb radiographs obtained preoperatively and at the final follow-up were used to the percentages of crossing points of the weight-bearing line and tibial plateau with respect to the medial border and mechanical femur-tibia angle. Preoperatively predicted and postoperatively measured wedge angles and gaps were compared. The clinical results were evaluated using the Hospital for Special Surgery (HSS) knee score and the Knee Society score. Results: At the 20.5 months (12–26.5) follow-up, the weight-bearing line on the tibial plateau was corrected from 17.3% to 61.3%, and the mechanical femur-tibia angle was corrected from 7.3° varus to 3.1° valgus. No significant difference in preoperative and postoperative measured values was observed ( p = 0.440 and p = 0.505). The mean HSS score increased from 66.7 to 88.8 ( p < 0.001). The knee score and function score of Knee Society increased from 62.0 to 88.7 ( p < 0.001) and from 60.2 to 91.7 ( p < 0.001), respectively. Conclusion: In open-wedge HTO, correction of angular deformity based on the PACS method could be an accurate correction method and the good clinical results could be obtained.